1998
DOI: 10.1137/s1064827595290711
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Approximation of the Diffusion Operator on Tetrahedra

Abstract: Linear Galerkin finite element discretizations of the Laplace operator produce nonpositive stiffness coefficients for internal element edges of two-dimensional Delaunay triangulations. This property, also called the positive transmissibility (PT) condition, is a prerequisite for the existence of an M -matrix and ensures that nonphysical local extrema are not present in the solution.For tetrahedral elements, it has already been shown that the linear Galerkin approach does not in general satisfy the PT condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 13 publications
(25 reference statements)
1
75
0
Order By: Relevance
“…Having applied the viscous term discretization to the Laplace operator, Delanaye et al [8] showed that a correction of the diamond-shaped control volume on Cartesian grids leads to the more positive scheme and obtained a robust discretization of the viscous terms in Navier-Stokes equations. Putti and Cordes [13] have proposed a modification of the control volume that allowed them to obtain the positive discretization of the Laplace equation on three-dimensional Delaunay meshes. In all these cases the choice of the control volume has been dictated by the geometry of grid cells.…”
mentioning
confidence: 99%
“…Having applied the viscous term discretization to the Laplace operator, Delanaye et al [8] showed that a correction of the diamond-shaped control volume on Cartesian grids leads to the more positive scheme and obtained a robust discretization of the viscous terms in Navier-Stokes equations. Putti and Cordes [13] have proposed a modification of the control volume that allowed them to obtain the positive discretization of the Laplace equation on three-dimensional Delaunay meshes. In all these cases the choice of the control volume has been dictated by the geometry of grid cells.…”
mentioning
confidence: 99%
“…N T and N represent the total number of triangles and nodes (or vertices) of T h , respectively, and T e , e = 1, …, N T , is a generic triangle of T h , with area We construct a dual mesh over T h , where a dual finite volume e i , i =1, ..., N, is associated with node i. It is the Voronoi polygon, defined as in [40], shown in Figure 2b. We call the dual finite volumes, (computational) cells.…”
Section: Computational Mesh Propertiesmentioning
confidence: 99%
“…and h km is a water depth value in the computational cell obtained by local mass balance, computed as explained in [14], as well as the Q sp coefficient in Equation (20). The initial condition is η = 0, and L(h km ) in Equation (20) is the water surface width corresponding to h km .…”
Section: The Fractional Time Step Proceduresmentioning
confidence: 99%
“…The dual finite volume e i , previously defined, is called the Voronoi cell or the Thiessen polygon [20]. The vertices of the Voronoi cells are the circumcenters of the Delaunay triangulation.…”
Section: Computational Mesh Properties and Computational Cellsmentioning
confidence: 99%
See 1 more Smart Citation